2013
DOI: 10.4103/0974-2727.119849
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Extended-Spectrum β-Lactamases and AmpC Production in Uropathogenic Isolates of Escherichia coli and Susceptibility to Fosfomycin

Abstract: Background:Urinary tract infection due to Escherichia coli is one of the common problem in clinical practice. Various drug resistance mechanisms are making the bacteria resistant to higher group of drugs making the treatment options very limited. This study was undertaken to detect ESBLs and AmpC production in uropathogenic Escherichia coli isolates and to determine their antimicrobial susceptibility pattern with special reference to fosfomycin.Materials and Methods:A total number of 150 E. coli isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 13 publications
7
36
2
Order By: Relevance
“…This result was in agreement with another study conducted by Gupta et al, (2013) who showed that of 52.6% of the isolates were ESBLs producer strains and 10% of strains were AmpC producer. Another investigation from Egypt revealed that 57.7% of isolates were Amp C enzyme producer (Fam et al, 2013 Singhal et al, (2005), who reported 5.7%, 5.9%, and 7% of the isolate were AmpC producer respectively.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This result was in agreement with another study conducted by Gupta et al, (2013) who showed that of 52.6% of the isolates were ESBLs producer strains and 10% of strains were AmpC producer. Another investigation from Egypt revealed that 57.7% of isolates were Amp C enzyme producer (Fam et al, 2013 Singhal et al, (2005), who reported 5.7%, 5.9%, and 7% of the isolate were AmpC producer respectively.…”
Section: Resultssupporting
confidence: 83%
“…Resistance to quinolones was recorded to be 91.1% to norfloxacin and 75.6% to ciprofloxacin. This was in consistent with Farzana et al, (2013), Gupta et al, (2013) and Chander and Shrestha (2013), who reported high level of resistance to quinolones more than 90%. Elsayed et al, (2017) reported similar resistance to ciprofloxacin (72.2%) but less resistance to norfloxacin (59%).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…22,23 In current study 15.90% Enterococci were isolated, found to be second most common organism causing UTI after E. coli. Among these enterococci, 69.09% and 76% of them were found resistant to levofloxacin and doxycycline respectively which are commonly and frequently prescribed drugs for UTI.…”
Section: Discussionmentioning
confidence: 99%